EPOS E NARRATIVA: FUNÇÕES SIGNIFICATIVAS DA PALAVRA - Schell, Denis (Organon, 2004)
This paper analyses the narratives by Gilgamesh as well as Homeric poems, consideringthe Epos as a vehicle for significant human values. Curing, enchanting, it can be said, therapeuticfunctions of the heroic word are examined side by side with the impetrative, pleasing, seductive withpersuasive character functions in the dialogues of the Mesopotamian and Mediterranean ancientepic poems.